The Portrayal of Feminine Touch in Y.O.U Beauty Indonesia and Philippines Advertisements - Supriyono, Nanda Meg Ryan Puspitasari; Larasati, Marcelina Pulcheria; Prasmato, Arafah (Lingua : Journal of Linguistics and Language, 2024)
This research aims to analyze the portrayal of feminine touch in the skin care advertisement Y.O.U Beauty with a case study in two countries, Indonesia and Philippines by using Erving Goffman’s theory on gender advertisement. The sample is taken from four posts under Y.O.U Beauty official Instagram account. The method that is used in this research is descriptive qualitative and the data are analyzed using content analysis to provide a detailed and systematic examination of the contents of the advertisements. The result shows that there are three key aspects including the connection between model and product, gesture, and color appearance that depict feminine touch in the advertisement of Y.O.U skin care products both in Indonesia and Philippines. In addition, the advertisement also demonstrates a shift in mindset and culture related to the usage of skin care products in society in recent years viewed from the choice of brand ambassadors who are men and women.